Bemisia tabaci Biotype Q is present in Costa Rica - Guevara Coto, José Andrés (2011)
Whiteflies are an insect group that comprises multiple species and biotypes, capable of affecting crops by phloem feeding, virus transmission and promotion of fungal colonization. The distribution of these pests is worldwide. In Costa Rica, a country located in the tropics, the most problematic whiteflies are Bemisia tabaci biotype B and Trialeurodes vaporariorum. In September 2009, two greenhouses in the Alfaro Ruiz region, northwest of the country’s capital, San Jose, were surveyed as part of a larger effort to determine the occurrence of species and races of whiteflies in this agronomically important region. In addition, the insect samples were analyzed to determine the presence of Tomato chlorosis virus (ToCV), a yield-affecting crinivirus transmitted by whiteflies. The results revealed the presence of the Q biotype of B. tabaci, and important invasive species, as well as the expected T. vaporariorum. Viral detection assays identified potentially viruliferous individuals for Tomato chlorosis virus. These results identified a new pest capable of harbouring plant viruses has been identified, as well as a viral agent (ToCV) in a region where it was not reported, and which might cause significant yield losses.